Conselhos municipais de educação: participação e cultura política - Betlinski, Carlos (2006)
The research had as study object Municipal Councils of Education of two cities of the metropolitan area of Sao Paulo and it was anchored in the participation and political culture concepts to evaluate the results produced by the implantation of those organs of the administration of the municipal education. MCE are inserted in the scenery of the Brazilian education system as instruments of democratization of the public politics, because to the those public spaces of relationship between State and civil society the control functions, fiscalization and normatization are attributed, making possible, with that, larger transparency and collegiate decisions in the education of the municipal district. The methodological process included interviews with the counselors' groups, observations, documental analysis and the application of instrument of evaluation of participation indicators in the education administration of the studied cities. Based on the modality of the critical theory the investigation looked for emphasizing aspects of the subjective political culture of two subgroups (counselors) of the national context, analyzing their thought and action in the counsels. Starting from the revision of the theoretical referential on representative democracy and participative democracy, the activities of CME were analyzed and classified the activities of CME as for those to matrixes. Critics and possibilities of overwhelming the elitist representative democracy understood are pointed as hegemonic in the studied reality. The results produced by the research point to a contradictory process among the political practices of the councils and of their counselors and the justifications of the Brazilian State for the implantation of those organs. The democracy conception and the hegemonic political culture visualized in the practices that guide the governors' relationship and of the civil society in the conduction of the public politics don't correspond to the theoretical-practical referential of the participative democracy. In one of the municipal districts, with the due safeguards, it was noticed the citizen valorization and meaning attribution potentially democratized for the piece of council, in the other, was observed the conservatism and the contradictions in relation to the participative democracy where represents as instrument of extension of the Executive's power and of legitimating of their decisions. The collegiate just signal for the production of a political culture, that, beside legal procedures (legislation) and of structural conditions (education, income, institutions) they could produce the participative democracy as condition to overcome the division among rulers and governed